The Effect of Leadership and Competence on Performance (Employee Study at the Village Office of Pagatan City, Kusan Hilir District, Tanah Bumbu Regency, South Kalimantan Province) - Karniah Karniah; Maskur Maskur; Sulastini Sulastini (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study was to analyze: 1) To analyze whether leadership partially affects the performance of leadership employees at the Pagatan City Village Office, Kusan Hilir District, 2) To analyze whether competence partially has a significant effect on the performance of leadership employees at the Pagatan City Village Office, Kusan District Downstream and 3) To analyze whether Leadership and Competence have a simultaneous effect on employee performance at the Village Office of Pagatan City, Kusan Hilir District. The method used in this research is quantitative with a total sample of 34 respondents using multiple regression analysis. The results of this study are 1) There is a positive and significant effect of the Leadership variable (X1) partially on the Performance variable (Y) Employees of the Village Office of Pagatan City, Tanah Bumbu Regency (0.039 <0.05) with the question Leaders have the skills to educate their subordinates well with a score The highest is an indicator that leadership is able to improve employee performance with the skills to educate subordinates in the Pagatan City Village Office, Tanah Bumbu Regency, 2) There is a positive and significant effect of the Competency variable (X2) partially on the Performance variable (Y) Employees of the Pagatan City Village Office, Regency Tanah Bumbu (0.022 <0.05) with the question that I have the ability to understand tasks in my field of work in detail, getting the highest score is an indicator that employee competence is good because most employees understand the tasks assigned to them and 3) There is a positive and significant influence variable Leadership (X1) and Competence (X2) simultaneously on Performance (Y) Employees of the Village Office of Pagatan City, Tanah Bumbu Regency (0.001 <0.05) this shows that leadership in the Village Office of Pagatan City, Tanah Bumbu Regency has increased employee competence so that indirectly improve the performance of his subordinates. Keywords: Leadership, Competence, Performance